Discovery of Simple Sequence Repeat Markers in the Endemic Durian Kura-Kura (Durio testudinarius Becc.) - Magandhi, Mahat; Sobir; Matra, Deden Derajat; Wahyu, Yudiwanti; Sudarmono (HAYATI Journal of Biosciences, 2025)
Durio testudinarius, known as Durian Kura-Kura, is a native Bornean durian species in the Malvaceae family with fruit at the base of the main stem. Recent advances in genomic-based next-generation sequencing are being used to conserve germplasm and enhance plant breeding. This method rapidly and cost-effectively sequences plant genomes, allowing for simple sequence repeat markers to be constructed in silico. This study aimed to design and evaluate novel, simple sequence repeat markers utilizing next-generation sequencing microsatellite data of D. testudinarius. A total of 20 sequences containing di-, tri-, tetra-, and penta-nucleotide motif repeats were selected and designed to generate primers using Primer3 online software. The PCR results of the twenty primers tested on D. testudinarius and 19 genomic DNA samples of species from the Malvales order showed successful amplification. These newly developed simple sequence repeat markers are crucial for genetic population analyses, determining population structure, and enhancing plant breeding programs and conservation strategies for D. testudinarius and its relative's germplasm resources.